Implementasi Clinical Pathway Tahun 2018 dalam Upaya Meningkatkan Mutu Pelayanan di Rumah Sakit Umum Daerah Koja - Arroyan Wardhana; Sri Rahayu; Ahdun Triguno (Lembaga Penelitian Universitas YARSI, 2019)
Improving the quality of patient services in hospitals is an important program implemented in hospitals. One indicator of improving hospital quality is the application of Clinical Pathway (CP) as an evaluation of hospital accreditation. Benefits of CP as a means of quality control and costs in improving hospital services. The general objective of this research is the preparation of a Clinical Pathway implementation plan in improving the quality of hospital services.This research method is qualitative with data collection techniques conducting in-depth interviews, observation and document review. The selection of informants in qualitative research, based on suitability and adequacy as many as 17 people. Analysis of CP implementation consists of inputs; which constitute human resources, processes; implementation of monitoring and evaluation, output; service quality after CP. The results of the study are based on inputs, processes and outputs that indicate implementation has been implemented in accordance with hospital accreditation, but needs optimization. Input factors analyzed will support the implementation of CP but need to uniformize the Clinical Pathway format, the evaluation monitoring process has not run optimally while the quality of service output is in accordance with the Clinical Pathway. Suggestions for Hospital Director to carry out Clinical Pathway understanding by holding workshops for all related parties and increasing the guidance and supervision of the implementation of Clinical Pathway, all units involved to coordinate with each other and implement Standard Operating Procedures (SPO) of CP for patient safety.